Assessment of the atmospheric air pollution level in Kyiv - Barabash, Olena; Khrutba, Viktoriia (Lviv Politechnic Publishing House, 2019)
Groups of plants, that regulate gas composition and the degree of air pollution, play a significant role in solving a complex spectrum of problems in the development of the modern city. The system “plant organism-urban environment” is indicative for the detection of dust pollution in atmospheric air of urban areas, manifesting the response of higher plants (morphological, anatomical, biochemical changes) used in urban landscaping.
Keywords: atmospheric air; dust pollution; leaf blades; small-leaved linden (Tilia cordata Mill.)